161P Regulatory interacting network between the immunomodulatory non-coding RNAs: miR-17-5p, MALAT1 and H19 lncRNAs in modulating the tumour microenvironment in TNBC. (15th December 2019) - Soliman, R; Youness, R A; El-Shazly, M; Handoussa, H; Gad, M
Abstract: Background: Triple-negative breast cancer (TNBC) patients are the least fortunate in terms of diagnosis, prognosis and treatment compared to other BC subtypes. Chemotherapy remains the standard treatment, with remarkable rate of resistance. Immunotherapy, on the other hand has shown promising approaches for this aggressive BC subtype. A critical determinant of the success of the immunotherapeutic approaches introduced recently in the clinics is the tumour microenvironment (TME). Our research group has recently highlighted the potential role of IL-10 in shaping the TME of TNBC patients. In this study, we focus on the main pro-inflammatory cytokine, tumour necrosis factor-α (TNF-α), in modulating TME in TNBC cells. In a more translational approach, ncRNAs have been casted as vital regulators of the immune system. A new frontier in the ncRNA world is the cross talk between miRNAs and lncRNAs. In this study, we aimed to investigate the role of microRNA-17-5p and its cross-talk with the oncogenic long non-coding RNAs: MALAT1 and H19 in regulating TNF-α in the TME of TNBC. Methods: Forty BC patients were recruited. In-silico analysis was performed. MDA-MB-231 cells were cultured and transfected with miR-17-5p oligonucleotides, MALAT1 and H19 siRNAs. Total RNA was extracted and quantified by qRT-PCR. Cellular viability, Colony forming ability and cellular migration were measured using MTT, colony forming assay and scratch assay respectively. Results: miR-17-5p was down-regulated while MALAT1, H19 and TNF-α were markedly upregulated in TNBC patients. In-silico analysis showed that miR-17-5p binds to MALAT1, H19 and TNF-α. Ectopic expression of miR-17-5p resulted in a significant reduction in H19, MALAT1 and TNF-α. Reciprocally, knocking down of MALAT1 or H19 resulted in a marked induction in miR-17-5p levels. However, MALAT1 and H19 siRNAs decreased TNF-α levels. Functionally, miR-17-5p resulted in a marked reduction in cellular viability, colony forming ability and cellular migration of TNBC cells. Conclusion: miR-17-5p/MALAT-1/H19/TNF-α represents an immunomodulatory loop that diverts the host immunity in favour of anti-tumour response. Legal entity responsible for the study: German University in Cairo. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.